Knowledge Management for SMEs about Building Rehabilitation - Alfredo Soeiro (2012)
The project is motivated by the increasing number of complex works of rehabilitation of buildings that require rapidand systematic access to specific knowledge. The approach is to facilitate access to proper knowledge throughcollaborative business networks formed by companies and research and development partners. This project aims at:(a) providing a learning community of fundamental knowledge and an organization of tacit knowledge of SMEs and (b)allowing closer business collaboration between SMEs and RDs. The project plans to develop solutions based oninformation technology and communication that are adequate for SMEs, including knowledge sharing and training forengineers.